Terapi target terhadap Sel Punca Kanker Kolorektal dengan Fitofarmaka – sebuah review sistematik - Martahadinan Martahadinan; Ika Silviadewi Inzaghi; Erik Prabowo; Ahmad Fathi Fuadi; Dimas Erlangga (Jurnal Biomedika dan Kesehatan, 2026)
Colorectal cancer (CRC) is the third most common malignancy but ranks second after lung cancer in terms of mortality, posing a significant public health burden due to its high incidence and death rates. Cancer stem cells play an important role in chemoresistance, tumor progression, and recurrence in CRC. 5-Fluorouracil (5-FU) is a primary chemotherapeutic agent used to kill cancer cells and reduce the risk of recurrence. Resistance to 5-FU remains a major obstacle in CRC treatment, highlighting the need for novel therapeutic strategies targeting cancer stem cells. This review draws on data collected from various electronic databases, covering studies published between January 1, 2015, and December 31, 2024. The search focused on colorectal cancer stem cells (CCSCs) and compared outcomes between monotherapy chemotherapy and chemotherapy combined with phytopharmaceuticals. Preclinical experimental studies published in English and available in full text were included, while case reports, case series, clinical studies, systematic reviews, meta-analyses, clinical guidelines, studies using human tumor tissue samples, and non-English or unavailable full-text articles were excluded. The results were that eight preclinical studies were included, comprising seven controlled experimental studies and one uncontrolled in vitro study. Four studies used 5-FU as a control in combination with different phytopharmaceuticals, including pseudolaric acid B (PAB), morin and MST-312, and diethylaminobenzaldehyde (DEAB), and baicalin. The remaining four studies evaluated phytopharmaceuticals in combination with alternative chemotherapeutic agents, including oxaliplatin with resveratrol, cisplatin with atractylenolide I (ATL-1), and rapamycin with curcumin, or investigated ginsenoside Rg3R as monotherapy. Cellular apoptosis was the primary outcome, while apoptosis-related signaling pathways were evaluated as secondary outcomes. Phytopharmaceuticals as a promising area of research in overcoming chemotherapeutic resistance. The findings reflect a shift in current therapeutic strategies, increasingly favoring phytopharmaceutical-based treatments to reduce drug resistance and enhance the efficacy of chemotherapy with minimal side effects.